Indie reframed : women's filmmaking and contemporary American independent cinema - Badley, Linda; Perkins, Claire (Claire Elizabeth); Schreiber, Michele (Traditions in American cinema., 2016)
Explores the films, practitioners, production and distribution contexts that currently represent American women's independent cinemaWith the consolidation of ÃǾ²Ơ℗indie' culture in the 21st century, female filmmakers face an increasingly indifferent climate. Within this sector, women work across all aspects of writing, direction, production, editing and design, yet the dominant narrative continues to construe ÃǾ²Ơ℗₋maverick' white male auteurs such as Quentin Tarantino or Wes Anderson as the face of indie discourse. Defying the formulaic myths of the mainstream ÃǾ²Ơ℗₋chick flick' and the ideological and experimental radicalism of feminist counter-cinema alike, women's indie filmmaking is neither ironic, popular nor political enough to be readily absorbed into pre-existing categories. This ground-breaking collection, the first sustained examination of the work of female practitioners within American independent cinema, reclaims the ÃǾ²Ơ℗₋difference' of female indie filmmaking. Through a variety of case studies of directors, writers and producers such as Ava DuVernay, Lena Dunham and Christine Vachon, contributors explore the innovation of a range of female practitioners by attending to the sensibilities, ideologies and industrial practices that distinguish their work - while embracing the ÃǾ²Ơ℗₋in-between' space in which the narratives they represent and embody can be revealed. Key Features Covers American women's independent cinema since the late 1970s Analyses the work of acclaimed but critically overlooked female practitioners such as Kelly Reichardt, Christine Vachon, Miranda July, Kasi Lemmons, Nicole Holofcener, Mira Nair, Lisa Cholodenko, Megan Ellison, Lynn Shelton, Ava DuVernay, Mary Harron and Debra Granik Distinguishes four different approaches to analysing women's independent cinema through: production and industry perspectives; genre and other classificatory modalities; political, cultural, social and professional identities; and collaborative and collectivist practices Contributors John Alberti, Northern Kentucky University Linda Badley, Middle Tennessee State University Cynthia Baron, Bowling Green State University Shelley Cobb, University of Southampton Corinn Columpar, University of Toronto Chris Holmlund, University of Tennessee-Knoxville Geoff King, Brunel University, London Christina Lane, University of Miami James Lyons, University of Exeter Kathleen A. McHugh, UCLA Kent A. Ono, University of Utah Lydia Papadimitriou, Liverpool John Moores University Claudia Costa Pederson, Wichita State University Claire Perkins, Monash University Sarah Projansky, University of Utah Maria San Filippo, Goucher College Michele Schreiber, Emory University Sarah E.S. Sinwell, University of Utah Yannis Tzioumakis, University of Liverpool Patricia White, Swarthmore College Patricia R. Zimmermann, Ithaca College Explores the films, practitioners, production and distribution contexts that currently represent American women's independent cinemaWith the consolidation of ÃǾ²Ơ℗₋indie' culture in the 21st century, female filmmakers face an increasingly indifferent climate. Within this sector, women work across all aspects of writing, direction, production, editing and design, yet the dominant narrative continues to construe ÃǾ²Ơ℗₋maverick' white male auteurs such as Quentin Tarantino or Wes Anderson as the face of indie discourse. Defying the formulaic myths of the mainstream ÃǾ²Ơ℗₋chick flick' and the ideological and experimental radicalism of feminist counter-cinema alike, women's indie filmmaking is neither ironic, popular nor political enough to be readily absorbed into pre-existing categories. This ground-breaking collection, the first sustained examination of the work of female practitioners within American independent cinema, reclaims the ÃǾ²Ơ℗₋difference' of female indie filmmaking. Through a variety of case studies of directors, writers and producers such as Ava DuVernay, Lena Dunham and Christine Vachon, contributors explore the innovation of a range of female practitioners by attending to the sensibilities, ideologies and industrial practices that distinguish their work - while embracing the ÃǾ²Ơ℗₋in-between' space in which the narratives they represent and embody can be revealed. Key Features Covers American women's independent cinema since the late 1970s Analyses the work of acclaimed but critically overlooked female practitioners such as Kelly Reichardt, Christine Vachon, Miranda July, Kasi Lemmons, Nicole Holofcener, Mira Nair, Lisa Cholodenko, Megan Ellison, Lynn Shelton, Ava DuVernay, Mary Harron and Debra Granik Distinguishes four different approaches to analysing women's independent cinema through: production and industry perspectives; genre and other classificatory modalities; political, cultural, social and professional identities; and collaborative and collectivist practices Contributors John Alberti, Northern Kentucky University Linda Badley, Middle Tennessee State University Cynthia Baron, Bowling Green State University Shelley Cobb, University of Southampton Corinn Columpar, University of Toronto Chris Holmlund, University of Tennessee-Knoxville Geoff King, Brunel University, London Christina Lane, University of Miami James Lyons, University of Exeter Kathleen A. McHugh, UCLA Kent A. Ono, University of Utah Lydia Papadimitriou, Liverpool John Moores University Claudia Costa Pederson, Wichita State University Claire Perkins, Monash University Sarah Projansky, University of Utah Maria San Filippo, Goucher College Michele Schreiber, Emory University Sarah E.S. Sinwell, University of Utah Yannis Tzioumakis, University of Liverpool Patricia White, Swarthmore College Patricia R. Zimmermann, Ithaca College